Renewable syngas production from electrified catalytic steam reforming of biomass pyrolysis volatiles - José Juan Bolívar Caballero; Fereshteh Talkhab; Hanmin Yang; Samina Gulshan; Pengcheng Cao; Thomas Lewin; Pär G. Jönsson; Weihong Yang (Chemical Engineering Journal Advances)
Pyrolysis of biomass plus catalytic reforming of its pyrolysis volatiles is a green alternative to produce solid (biochar) and gaseous (syngas) fuels that have several valuable applications; however, this catalytic process suffers from fast deactivation, and its energy consumption is yet to be studied, factors that determine the process’s feasibility in industrialisation. To address these issues, the direct electrification of a 3D-printed FeCrAl heater coated with 15.5 % Ni/Al2O3 was tested in a parametric study in the catalytic steam reforming of biomass pyrolysis volatiles, in order to investigate the effect of the S/B ratio and space–time on the syngas yield and composition. Complete bio-oil reforming was obtained at a biomass feed rate of ≤ 1 g min−1 and a S/B ratio of ≥ 2, and stability close to 100 % was estimated after over four hours of operation. Nonetheless, the produced syngas is rich in C1 – C3 gases and moderately low in H2 (≈ 2 wt %). The effect of the catalyst’s structure on the bio-oil reforming and heat efficiency was complemented using CFD simulations and compared to a simple geometry based on commercial extruded monoliths. Finally, the biomass-derived syngas upgrading to H2 production was assessed using different process simulations and compared to existing H2-producing technologies in terms of energy efficiency and emissions.